Clinically Relevant Levels of 4-Aminopyridine Strengthen Physiological Responses in Intact Motor Circuits in Rats, Especially After Pyramidal Tract Injury. (April 2017) - Sindhurakar, Anil; Mishra, Asht M.; Gupta, Disha; Iaci, Jennifer F.; Parry, Tom J.; Carmel, Jason B.
Background . 4-Aminopyridine (4-AP) is a Food and Drug Administration–approved drug to improve motor function in people with multiple sclerosis. Preliminary results suggest the drug may act on intact neural circuits and not just on demyelinated ones. Objective . To determine if 4-AP at clinically relevant levels alters the excitability of intact motor circuits. Methods . In anesthetized rats, electrodes were placed over motor cortex and the dorsal cervical spinal cord for electrical stimulation, and electromyogram electrodes were inserted into biceps muscle to measure responses. The motor responses to brain and spinal cord stimulation were measured before and for 5 hours after 4-AP administration both in uninjured rats and rats with a cut lesion of the pyramidal tract. Blood was collected at the same time as electrophysiology to determine drug plasma concentration with a goal of 20 to 100 ng/mL. Results . We first determined that a bolus infusion of 0.32 mg/kg 4-AP was optimal: it produced on average 61.5 ± 1.8 ng/mL over the 5 hours after infusion. This dose of 4-AP increased responses to spinal cord stimulation by 1.3-fold in uninjured rats and 3-fold in rats with pyramidal tract lesion. Responses to cortical stimulation also increased by 2-fold in uninjured rats and up to 4-fold in the injured. Conclusion . Clinically relevant levels of 4-AP strongly augment physiological responses in intact circuits, an effect that was more robust after partial injury, demonstrating its broad potential in treating central nervous system injuries.